Women in Buddhist Literature - Law, Bimala Churn, (Brill | Manohar Publishers & Distributors, 2024)
Two prominent names, Khema and Uppalavanna, were popular bhikkunis appointed by Buddha in his fold. But the major question that arises is the condition of women in the Buddhist literature. This mini-volume covers the most crucial aspect of the Buddhist world, which is the depiction of women. The author of this book covers the Pali sources composed by the early Sanghas to reconstruct the position of women in Buddhist society. Firstly, this volume touches on the issues pertaining to marriage, slavery, the position of nautch girls and prostitution, and the education system in the Buddhist literature. And finally, it features the relationship between women and Buddhism, the nunnery system, and a description of the famous Buddhist women.